Enhanced inter-regional coupling of neural responses and repetition suppression provide separate contributions to long-term behavioral priming - Stephen J. Gotts (Nature Portfolio, 2021)
Gotts et al. test different theoretical model predictions for repetition-associated alterations in functional and/or effective brain connectivity using fMRI. They report that the generated data is most consistent with a Synchrony model-based prediction and provide data which informs the refinement of all models tested.